Utilização digestiva, metodologias de avaliação "in vitro" de dietas e caracterização da microbiota cecal em coelhos suplementados com Lithothamnium. - Ana Carolina Castro Euler (2009)
In order to study the potential of Lithothamnium sp. as functional foods, where experiments were conducted to evaluate the nutritional diets with increasing levels (0.25, 0.50, 0.75 and 1.00%) for inclusion of Lithothamnium sp. in rabbit feeding. For this, we analyzed the composition of the trace minerals Lithothamnium sp., the apparent digestibility of diets and production parameters in young rabbits, and the influence of the genetic diversity Lithothamnium cecal and ileal morphometry. It also evaluated the alkaline phosphatase as an indicator of serum calcium and phosphorus. In addition to studying the effects of Lithothamnium the feeding of rabbits, were evaluated different methods of evaluation of food (Technical Mauricio et al. (1999) for gas production, with different methods of conservation of cecal contents for the inoculum preparation and technique Tilley and Terry (1963)). However, we can conclude that the Lithothamnium trace element presents no harm to animal nutrition, the levels tested for inclusion in experimental diets showed no satisfactory results to be considered a functional food, the techniques of in vitro evaluation of foods have been shown to be effective for determine the digestibility coefficients for rabbits, the cecal contents of the freeze as a source of inoculum showed satisfactory results, allowing its use in the standardization of the inoculum, the technique of Tilley and Terry showed only effective within 24 hours of fermentation during the first stage of development; the Lithothamnium sp. showed no beneficial effect on the intestinal villi and in the level of 1% of inclusion undermined the development of the same, the technique of gel electrophoresis withdenaturing gradient (DGGE) was perfectly adequate for analysis of DNA from the cecal microbiota of rabbits and profile of genetic diversity showed greater richness in samples obtained from the referencediet and lower diversity in the sample derived from the diet with 0.5% for inclusion of Lithothamnium; the serum alkaline phosphatase showed an inverse relationship with serum levels of calcium and phosphorus, may represent a potentially useful parameter in determining the biodisponibillidade these elements.